1829. A Systems Approach to Nursing Home Antimicrobial Stewardship. (26th November 2018) - Gravenstein, Stefan; Manning, David; Baier, Rosa R; Crnich, Christopher; Davidson, H Edward; LaPlante, Kerry; Dosa, David; Jump, Robin
Abstract: Background: Up to 70% of nursing home (NH) residents receive one or more courses of antibiotics (ATB) annually, of which over half may be inappropriate and risk harm. The current availability of in-house NH data is often insufficient to measure and track appropriateness, due to incomplete data or unusable formatting. Our 3-year project to improve antimicrobial stewardship (AMS) used the Centers for Disease Control and Prevention's (CDC) Core Elements of AMS for NHs, with guided input from NH providers to develop and implement an electronic ATB de-escalation decision support tool that also captures otherwise inaccessible data. Methods: Our baseline assessment identified wide variation in providers' knowledge, attitudes, and beliefs regarding ATB prescribing, leading us to identify de-escalation as the most feasible NH AMS intervention. Using facilitated open-ended conversations with leaders from three NH corporations, we developed an electronic decision support tool to systematically prompt de-escalation 48–72 hours post-prescribing. Subsequent site visits with NH clinical teams at a convenience sample of sites allowed us to explore how to incorporate decision support into their electronic health record (EHR). Results: We developed a tool anchored on data capture for the "acute change in condition" that triggers prescriber interactions. It uses clinical and laboratory data to prompt structured communication between nurses and prescribers. Placing this tool in the EHR reduced duplicate charting, enabled guidance from McGeer and Loeb criteria, and promoted its adoption into practice while ensuring data capture to assess appropriateness of ATB prescribing. Conclusion: Our electronic decision support tool captures clinical and laboratory data, which it then uses to systematically prompt conversations about de-escalation between nurses and prescribers, reducing variation in practice. Upon completion, the assessment ensures availability of data to assess, track, and report appropriate prescribing practices among prescribers. This tool proved acceptable to NH providers in three different corporations, suggesting feasibility of further expansion of this approach to a broader group of NH providers. Disclosures: H. E. Davidson, sanofi pasteur: Collaborator, Research support. Seqirus: Collaborator, Research support.